The role of the lateral tarsal strip procedure in modern ophthalmic plastic surgery—A review - Kopecký, Adam; Rokohl, Alexander C.; Heindl, Ludwig M. (Frontiers in Ophthalmology, 2022)
Introduction: Lateral Tarsal Strip is one of the basic surgical techniques in ophthalmic plastic surgery. It is used in many indications, predominantely in ectropion repair. Even though there are alternatives, it probably one of the most popular techniques in ophthalmic plastic surgery. The lateral tarsal strip is also part of bigger surgical procedures (such midfacelifting, entropion surgery, reconstruction surgery or a part of some surgical approaches to the orbit). The aim of this review is to assess the most common ways of usage of lateral tarsal strip, to cover its alternatives and to discuss the future of this technique. Methods: we have search Pubmed and Web of Science and went through articles about lateral tarsal strip. We have also searched for other techniques in that lateral tarsal strip is used and included these articles in our review. We have analyzed the major articles and made a review about the topic. Results: As a natural part of many advanced surgical techniques and as a major surgical technique for lower eyelid ectropion repair, the lateral tarsal strip remains and important part of the modern ophthalmic plastic surgery.